Rhamnose biosynthesis in mycoplasmas requires precursor glycans larger than monosaccharide. Issue 5 (19th July 2013) - Jordan, David S.; Daubenspeck, James M.; Dybvig, Kevin
Summary Despite the apparent absence of genes coding for the known pathways for biosynthesis, the monosaccharide rhamnose was detected in the d configuration in Mycoplasma pneumoniae and Mycoplasma pulmonis, and in both the d and l configurations in Mycoplasma arthritidis. Surprisingly, the monosaccharide glucose was not a precursor for rhamnose biosynthesis and was not incorporated at detectable levels in glucose‐containing polysaccharides or glycoconjugates. In contrast, carbon atoms from starch, a polymer of glucose, were incorporated into rhamnose in each of the three species examined. When grown in a serum‐free medium supplemented with starch, M. arthritidis synthesized higher levels of rhamnose, with a shift in the relative amounts of the d and l configurations. Our findings suggest the presence of a novel pathway for rhamnose synthesis that is widespread in the genus Mycoplasma.